Work-related Musculoskeletal Disorders, Work Ability and Associated Factors among Hairdressers of South Delhi: A Cross-sectional Study - Sana Zareen; Sheetal Kalra; Richa Hirendra Rai; Deepak Raghave; Sonia Pawaria; Usha Panihar; Sajjan Pal (Journal of Clinical and Diagnostic Research)
Introduction: Work-related Musculoskeletal Disorders (WMSDs) are highly prevalent occupational health issues that significantly impair quality of life and work productivity. Hairdressers, due to prolonged standing, repetitive movements and awkward postures, are particularly vulnerable to these disorders. Despite their growing numbers in metropolitan India and a largely unorganised workforce, there is a paucity of research on the prevalence and impact of WMSDs in this population. The present study addresses this gap by evaluating the prevalence of musculoskeletal disorders among hairdressers, their work ability and associated factors. Aim: To determine the prevalence of WMSDs, Work Ability Index (WAI) and the associated risk factors among hairdressers in South Delhi, based on factors identified in previous literature, including prolonged standing, repetitive movements, awkward postures, forceful exertion, inadequate breaks and high workload. Materials and Methods: This cross-sectional study was affiliated with the School of Physiotherapy at Delhi Pharmaceutical Sciences and Research University, New Delhi, India and conducted in South Delhi between July 2023 and December 2023 to assess the prevalence of WMSDs and the associated factors among hairdressers. A total of 316 participants, aged 18- 40 years, who communicated in Hindi or English and consented to participate, were included. Data were collected using a self-structured questionnaire, the Nordic Musculoskeletal Questionnaire (NMQ) and the WAI. Demographic variables such as age, gender, marital status, education and Body Mass Index (BMI) were considered. Statistical analysis was performed using Pearson’s correlation coefficient, with a significance level of p<0.05. Results: A total of 210 participants (66.7%) reported musculoskeletal disorders, primarily lower back pain, which affected 108 participants (34.3%), with 129 participants (61.3%) experiencing symptoms for one to seven days. The average WAI score was 32.2 (moderate), with 78 participants (24.8%) having poor workability. Prolonged standing was reported as the most common risk factor by 78 participants (24.68%), followed by awkward posture, noted by 58 participants (18.35%). Work ability was negatively affected by longer job hours, older age, health issues and poor exercise habits but was positively associated with higher education, better health behaviour and more work experience. Conclusion: The study reveals a high prevalence of musculoskeletal disorders among hairdressers in South Delhi, with significant correlations between work ability and factors such as job hours, age, health issues and education. Effective ergonomic interventions and health improvements are crucial for enhancing work ability and reducing injury rates in this profession.